PERANCANGAN RAK PERALATAN MAKAN YANG ERGONOMIS DAN HYGENIS - Waskito, Febrianto Puji; Sukania, I Wayan; Widodo, Lamto (Universitas Tarumanagara, 2023)
New days the cutlery rack as a storage place for cutlery such as plates, cups and spoons. Cleanliness of cutlery is a very important and influential part of food and drink, cutlery that is not washed clean can cause organisms or germs that are left behind to multiply and contaminate food. The results of the questionnaire 59% stated that it was difficult for the community to arrange cutlery. This happens because people place cutlery in a messy or not well-organized manner. In this study, a redesign of the existing food equipment racks was carried out. The design was carried out using the ergonomics method, the AHP reverse engineering method and VDI 2221. The results of the research and redesign of cutlery rack products that had been carried out using the AHP method were used to determine community needs analysis while to find out the design to be made was carried out by ergonomics method, reverse engineering, and VDI 2221. After these methods were carried out, the product design results were obtained with a length of 440 mm, a width of 550 mm, and a height of 600 mm. Furthermore, the product is made with the concept that has been selected, namely variant concept 3 using materials such as teak wood and UV Sterilizer lamps. This product targets people who need a neat and clean place to store food equipment.